Sex Differentiation by Ischio-pubic Index: A Radiological study over the Population of Bihar - Kumar, Gautam; Kumar, Avinash; Patil, Amit; Kumar, Binay; Kumar Rastogi, Ashok; Kumar, Prabhat (Journal of Indian Academy of Forensic Medicine, 2020)
Identification is establishment of identity of a person with the help of different physical characteristics. The different physical characteristics of human skeleton between both the sexs is the reason of Sexual dimorphism. Many researchers have studied and observed the different parameters for sexual dimorphism in different bones. Pelvis is most important bone for determination of sex because the sexual dimorphism is present even in fetal stage. In modern era of advancement, pathological autopsy is shifting towards the virtual autopsy in which CT scan, MRI and X-rays are replacing the conventional autopsy instruments. The present study was conducted with an aim to establish sex differentiation criteria in population of Bihar based on ischio-pubic index. 200 AP view pelvic digital radiographs were analysed in the present study, and the ischio-pubic index was calculated by measuring the length of pubis and ischium using the DICOM software. Ischio-pubic Index of pelvis in male and female sex is 94.04±11.02 and 114.16±14.85 respectively. The differences between males and females with respect to the ischio-pubic index are statistically significant (p<0.0001).